Interdisciplinary Perspectives on Sustainable Tourism: A Critical Literature Review and Research Opportunities - Gyanandre Tripathi; Amrita Dave (AG Volumes, 2026)
Maintaining a high degree of consumer happiness, increasing awareness of sustainability issues, and promoting sustainable tourist behaviors among them are all necessary for sustainable tourism. A comprehensive analysis of sustainable tourism is uncommon, but some previous studies have measured it in different parts of the world. In order to assess the state of the field and offer recommendations for further research on sustainable tourism, the study is based on a thorough examination of the literature.This study significantly advances the field of sustainable tourism research. It provides a study avenue to develop the field's literature, which is advantageous for future researchers. The crucial areas that scientific research studies could further investigate are the broad domains of sustainability, concerns pertaining to sustainable infrastructure and services, livelihood, and management of tourism destinations. The study's findings demonstrate that most research is shallow in terms of appropriate analysis, methodology, geographic variations, empirical analysis, and practical application. The key objective of this paper is to study uncovered areas in interdisciplinary sustainable tourism research and lay a strong foundation for future inquiries.